Cooking behaviours after Diabetes Prevention Program (DPP) participation among DPP participants in Baltimore, MD - Lauren E Russell; Jillian Tse; Janice Bowie; Caroline R Richardson; Amy Trubek; Nisa Maruthur; Julia A Wolfson (Cambridge University Press, 2023)
Abstract Objective: The Diabetes Prevention Program (DPP) is a widely implemented 12-month behavioural weight loss programme for individuals with prediabetes. The DPP covers nutrition but does not explicitly incorporate cooking skills education. The objective of the current study is to describe food and cooking skills (FACS) and strategies of recent DPP participants. Design: Photo-elicitation in-depth interviews were conducted from June to August, 2021. Setting: Baltimore, MD, USA. Participants: Thirteen Black women who participated in DPP. Results: The DPP curriculum influenced participants' healthy cooking practices. Many participants reported shifting from frying foods to air-frying and baking foods to promote healthier cooking and more efficient meal preparation. Participants also reported that their participation in DPP made them more mindful of consuming fruits and vegetables and avoiding foods high in carbohydrates, fats, sugars and Na. With respect to food skills, participants reported that they were more attentive to reading labels and packaging on foods and assessing the quality of ingredients when grocery shopping. Conclusions: Overall, participants reported changing their food preferences, shopping practices and cooking strategies to promote healthier eating after completing the DPP. Incorporating hands-on cooking skills and practices into the DPP curriculum may support sustained behaviour change to manage prediabetes and prevent development of type 2 diabetes among participants.